HUBUNGAN POLA ASUH ORANGTUA DENGAN KEMAMPUAN BINA DIRI ANAK AUTIS DALAM KELUARGA DI LEMBAGA TERAPI - AYU OKTAVIANTI, RIDHANING (Jurnal Pendidikan Khusus, 2016)
Abstract: Parents’ caretaking pattern was the parents’ effort to maintain and guide the children consistently and persistently since born to teenager. This research had purpose to know the existence of relationship between parents’ caretaking pattern and self guide ability of autism children. The subject of this research was the autism children in 5 – 8 years old in four therapy institutions Sidoarjo those were the therapy institution of Putra Harapan, Quantum, Cita Hati, and Esya. The technique of data analysis used was statistic non parametric with n = 12 and α = 5% and it was analyzed with Spearman Rank formula. The result of research data analysis to authorizer caretaking pattern was obtained ρ = - 0,0603, permissive caretaking pattern was obtained ρ = - 0,4012 and authoritative caretaking pattern was ρ =  0,4615. All of them were smaller than ρ table either in significant level 5% = 0,591 or 1% = 0,777. The interpretation was ρ counted < ρ table which meant that Ho was refused and Ha was accepted. The research data analysis indicated that the correlation between variable X (caretaking pattern: authorizer, permissive, and authoritative) and variable Y (self guide ability) was in high category and there was real / significant relationship between parents’ caretaking pattern and self guide ability of autism children in the family in therapy institution Sidoarjo.   Keywords: Parents’ caretaking pattern, self guide of autism